Kinematics and kinetics of taekwon-do side kick - Wasik, J. (Journal of Human Kinetics, 2011)
The aim of the paper is to present an analysis of the influence of selected kinematic factors on the side kick technique. This issue is especially important in the traditional version of taekwon-do, in which a single strike may reveal the winner. Six taekwon-do (International Taekwon-do Federation) athletes were asked to participate in this case study. Generally accepted criteria of sports technique biomechanical analysis were adhered to. The athletes executed a side kick three times (in Taekwon-do terminology referred to as yop chagi) in a way which they use the kick in board breaking. The obtained data were used to determine the mean velocity changes in the function of relative extension length of the kicking leg. The maximum knee and foot velocities in the Cartesian coordinate system were determined. The leg lifting time and the duration of kick execution as well as the maximum force which the standing foot exerted on the ground were also determined. On the basis of the obtained values, mean values and standard deviations were calculated. The correlation dependence (r=0.72) shows that greater knee velocity affects the velocity which the foot develops as well as the fact that the total time of kick execution depends on the velocity which the knee (r = -0.59) and the foot (r = - 0.86) develop in the leg lifting phase. The average maximum speed was obtained at the length of the leg equal to 82% of the maximum length of the fully extended leg. This length can be considered the optimum value for achieving the maximum dynamics of the kick.